Effective electrical conductivity of transversely isotropic rocks with arbitrarily oriented ellipsoidal inclusions. (June 2019) - Giraud, A.; Sevostianov, I.; Kushch, V.I.; Cosenza, P.; Prêt, D.; Barthélémy, J.F.; Trofimov, A.
Highlights: The electrical conductivity tensor of a transversely isotropic material that contains inhomogeneities of arbitrary orientation is determined Mudstone rock is modeled as a transversely isotropic multiphase composite. Two sources of effective anisotropy of the conductivity tensor are considered, matrix anisotropy and shape, orientation distribution of inclusions. In the case of low aspect ratio of inhomogeneity, contribution of inclusion phases to effective anisotropy may be significant. Mori–Tanaka–Benveniste, Maxwell, and differential homogenization schemes are used to calculate electric conductivity and compared. Abstract: This paper addresses the problem of the electrical conductivity tensor calculation for a transversely isotropic material that contains inhomogeneities of arbitrary orientation. For this goal, we first construct the electrical conductivity contribution tensor for an arbitrarily oriented isolated ellipsoidal anisotropic inhomogeneity embedded in a transversely isotropic matrix. The general case of an orthotropic ellipsoidal inhomogeneity unaligned in an anisotropic matrix with different classes of symmetry can be considered. This solution is used as the basic building block of various homogenization techniques: the Mori–Tanaka–Benveniste scheme, Maxwell scheme, and differential scheme. The approach is illustrated by an application to a transversely isotropic mudstone rock, composed of a clay matrix containing inhomogeneities of calcite and quartz. We analyse the origins of the extent of anisotropy of the effective conductivity tensor, distinguishing among the shape, orientation distribution, and anisotropy of the inhomogeneities on the one hand and the anisotropy of the matrix on the other hand. Numerical results show that the orientation distribution of the inhomogeneities significantly affects the overall anisotropy in the case of inhomogeneities with low aspect ratio(s). Limiting cases of aligned and randomly oriented inhomogeneities provide bounds of the extent of anisotropy for the overall conductivity tensor.